Solve the equation 7x + 6 = 1 + 2x

7x + 6 = 1 + 2x7x + 6 -2x = 15x + 6 = 15x = 1-65x = -5x = -1

Answered by Thomas R. Maths tutor

2512 Views

See similar Maths GCSE tutors

Related Maths GCSE answers

All answers ▸

When will I ever need to use this in real life?


How do you solve a quadratic equation?


Solve the simultaneous equations 4x + 5y = 13 and 3x - 2y = 27.


write log2(5) +log2​​​​​​​(3) in its simplest form


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo
Cookie Preferences